A meninice mentida e o futuro profanado:as narrativas de Valêncio Xavier - Fernanda Borges (Estudos de Literatura Brasileira Contemporânea)
The works of ValêncioXavier are characterized, in formal terms, by usingvarious types of images (drawings, photographs, newspaper articles, flipbooks), elements that make hybrid narratives. Such artifacts are arranged inorder to compose an album in the novelMinha mãe morrendo e o menino mentidoand an obituary inMeu 7º dia: uma novella rébus. From a lied childhood to adesecrated funeral, Valêncio Xavier lights and reworks childhood memories anddesigns and mocks the inevitable future. Thus, this study aims to discussstructural and thematic attributes of the works of this Brazilian author to reflecton these narrative albums that create the past and the future.